2014
DOI: 10.1111/jog.12625
|View full text |Cite
|
Sign up to set email alerts
|

Age‐dependent association of MDM2 promoter polymorphisms and uterine leiomyoma in South‐East Iran: A preliminary report

Abstract: MDM2 T309G polymorphism was not associated with UL and MDM2 40-bp Indel polymorphism could be an age-related risk factor for UL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 41 publications
0
23
2
Order By: Relevance
“…Although there are several reports about the association between polymorphisms of various cell cycle regulator proteins and UL [20,21], published reports about the association between p21 and UL are rare. The current study aimed to investigate the possible effects of p21 C98A and C70T polymorphisms and UL.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Although there are several reports about the association between polymorphisms of various cell cycle regulator proteins and UL [20,21], published reports about the association between p21 and UL are rare. The current study aimed to investigate the possible effects of p21 C98A and C70T polymorphisms and UL.…”
Section: Introductionmentioning
confidence: 90%
“…Since ULs are monoclonal tumors originated from uninhibited proliferation of a single myometrial cell; some investigations have been proposed that the imbalance in cell cycle regulation could be a primary event in the leiomyoma development [10]. There are several reports about the possible effects of different polymorphisms in genes encoding cell cycle regulatory proteins on the susceptibility to different tumors [10][11][12].…”
Section: Introductionmentioning
confidence: 98%
“…Growth factors may typically stimulate the angiogenesis of leiomyoma cells as compared with adjacent normal cells (Boehm et al, 1990;Di Lieto et al, 2005). Numerous investigations have revealed that both chromosome abnormalities in UL patients as well as genetic factors play key roles in UL pathogenesis in different countries, such as Iran (Gan et al, 2015;Salimi et al, 2015;Yaghmaei et al, 2015;Salimi et al, 2016). It is believed that ACE activity may be related to tumor growth and ACE inhibitors as well as angiotensin receptor blockers, thereby contributing to the suppression of tumor growth.…”
Section: Association Of Ace I/d and Agtr1 A1166c Gene Polymorphisms Amentioning
confidence: 99%
“…There are numerous VEGF polymorphisms, some of which are associated with altered VEGF expression [16]. A number of genetic studies have revealed the association between UL development and genetic polymorphisms; for example, VEGF [17], estrogen receptors [18,19], XRCC1 and p53 [20], CYP1A1 [21], Catechol-O-methyl transferase [22] and MDM2 [23] genes.…”
Section: Introductionmentioning
confidence: 99%